(Poly)phenol metabolomic signature in the brain of a parkinson´s disease model - Rocha, Bernardo André Botelho Soares (2023)
The occurrence of neurodegenerative diseases (NDs), including Parkinson's disease (PD), is increasing among our population at very high rates. Increased life expectancy, genetic predisposition, exposure to chemicals and environmental factors as well as lifestyle, are correlated with the progression of these diseases. However, we still do not fully understand how these causes can influence mechanisms adjacent to these pathologies, making it difficult to find a cure or an effective treatment. Epidemiological and observational studies have demonstrated the ability of polyphenols and their derivatives, namely low-molecular weight (poly)phenol metabolites (LMWPM) to promote health benefits. So far, the evidence of neuroprotective effects of some LMWPM have been described in preclinical PD models. In this project, we aim to i) identify and quantify the presence of LMWPM within the brain, and ii) evaluate the neuroprotective effects of a polyphenol- rich diet consumption using a PD rodent model. PD-like pathology was induced by injecting mice intraperitoneally with MPTP (4x15 mg/kg). We also aim to identify and quantify the presence of LMWPM within the brain. Mice injected with the toxin and fed berry-enriched diet, compared to those injected with MPTP and fed standard diet, showed a decrease in the concentration of certain pro-inflammatory mediators (IL-23 (at 24 hours) and CCL22 (at 7 days)). Additionally, it has been demonstrated that berries were effective in maintaining Tyrosine Hydroxylase (TH) levels and the number of microglia/macrophages cells, as well as their body cell area, at values closely resembling those noted in the control group. The metabolomic profiling of the LMWPM in plasma and brain revealed 11 metabolites present in both the brain and blood. To the best of our knowledge the metabolite 2,4 dihydroxybenzoic acid and trihydroxybenzaldheyde have been described for the first time in the brain. Three metabolites: benzoic acid, dihydrocaffeic acid and pyrogallol show higher concentrations in the brain compared to plasma. Finally, none of the LMWPM showed different concentrations in mice injected with MPTP and supplemented with berries compared with mice fed on standard food and injected with MPTP. Our results showed that a (poly)phenol-rich diet could attenuate different hallmarks in PD. However, further studies are needed to disclose the effects of LMWPM and whether they may help to averting or delay the initiation of NDs such as PD.